PENGARUH LATIHAN BOX DRILL TERHADAP POWER OTOT TUNGKAI PADA TIM SEPAK TAKRAW MAN 1 MUARA FAJAR PEKANBARU - Ittaqwa Ittaqwa; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is "Box drill exercises against the strength of leg muscles in the MAN 1 Muara Fajar Pekanbaru takraw team?" So that athletes in the future can perform and play much better and most importantly after research and discover if there is an improvement muscle strength of the athlete in the sepak takraw game, so that it can match the match of the opponent and in the future maximum results can to achieve. The form of this research is (using the only group pretest post-test design approach) with a population of Sepak Takraw players MAN 1 Muara Fajar Pekanbaru. The data in this research are all populations of 8 people. The instrument used in this research was to use the Vertical Jump test, which aims to determine the effect of exercises with the drill on leg muscle strength on the Sepak Takraw team MAN 1 muara fajar Pekanbaru. The data were then processed with statistics to test normality using the lilifours test at a significant level of 0.05 α. The hypothesis proposed is that there is the effect of exercises with the boxing drill on leg muscle strength in the sepak takraw team MAN 1 dawn of Pekanbaru. Based on the normal test analysis, the data produce X Lhitung of 0.1832 and Ltable of 0.285, which means Lhitung <Label. while the Y variable Lhitung produces 0.1526 and L table of 0.285. This means Lhitung <LTable. Based on the analysis of statistical data, there is an average variable X 16.62 and the average variable Y is 18.94, after which the data is normally distributed. There is the effect of Box Drill Exercises on Leg Muscle Power in the Sepak Takraw Team MAN 1 Muara Fajar Pekanbaru.Keywords: Box drill exercises, Strength of leg muscles